Investigations of spread of canine Brucellosis caused by Brucella canis in territory of Municipality of Požarevac - Živojinović Slobodan; Radojičić Sonja; Živojinović Milena; Kirćanski Jasmina (Veterinarski Glasnik, 2006)
The paper examines the presence and distribution of infections caused by Brucella canis in different categories of dogs in the territory of the Municipality of Požarevac. A total of 151 dogs were examined, and 74 blood serums originated from dogs of known owners and 77 from stray dogs. The investigations were carried out also on 40 samples of full blood of stray dogs, as well as fetal organs and reproductive organs of a serologically positive female following hysterectomy. Investigations included a clinical examination of the dogs, rapid serum agglutination, slow serum agglutination, and isolation of the cause. In all the examined dogs, the rapid agglutination test gave a positive result in 16.55% of the examined samples, the slow agglutination test 11.25%, which is an extremely high percentage in comparison with other regions of our country. Therapy using antibiotics, zoohygienic measures, castration or hysterectomy (as attempts to avoid residue and break the chain of the transfer of the infection) are conditions for out rooting the disease. Control of stray dogs is necessary, as they present the basic source of the infection. The results obtained in the course of these investigations indicate the absolute justification of including this contagious disease in the group of diseases whose reporting is compulsory.